Structural basis of Zn(II) induced metal detoxification and antibiotic resistance by histidine kinase CzcS in Pseudomonas aeruginosa. - Dan Wang; Weizhong Chen; Shanqing Huang; Yafeng He; Xichun Liu; Qingyuan Hu; Tianbiao Wei; Hong Sang; Jianhua Gan; Hao Chen (PLoS Pathogens, 2017)
Pseudomonas aeruginosa (P. aeruginosa) is a major opportunistic human pathogen, causing serious nosocomial infections among immunocompromised patients by multi-determinant virulence and high antibiotic resistance. The CzcR-CzcS signal transduction system in P. aeruginosa is primarily involved in metal detoxification and antibiotic resistance through co-regulating cross-resistance between Zn(II) and carbapenem antibiotics. Although the intracellular regulatory pathway is well-established, the mechanism by which extracellular sensor domain of histidine kinase (HK) CzcS responds to Zn(II) stimulus to trigger downstream signal transduction remains unclear. Here we determined the crystal structure of the CzcS sensor domain (CzcS SD) in complex with Zn(II) at 1.7 Å resolution. This is the first three-dimensional structural view of Zn(II)-sensor domain of the two-component system (TCS). The CzcS SD is of α/β-fold in nature, and it senses the Zn(II) stimulus at micromole level in a tetrahedral geometry through its symmetry-related residues (His55 and Asp60) on the dimer interface. Though the CzcS SD resembles the PhoQ-DcuS-CitA (PDC) superfamily member, it interacts with the effector in a novel domain with the N-terminal α-helices rather than the conserved β-sheets pocket. The dimerization of the N-terminal H1 and H1' α-helices is of primary importance for the activity of HK CzcS. This study provides preliminary insight into the molecular mechanism of Zn(II) sensing and signaling transduction by the HK CzcS, which will be beneficial to understand how the pathogen P. aeruginosa resists to high levels of heavy metals and antimicrobial agents.